2022
DOI: 10.1186/s12967-022-03457-w
|View full text |Cite
|
Sign up to set email alerts
|

Junctional adhesion molecule-like protein promotes tumor progression via the Wnt/β-catenin signaling pathway in lung adenocarcinoma

Abstract: Background Lung adenocarcinoma (LUAD) is a heavy social burden worldwide. Because the mechanisms involved in LUAD remain unclear, the prognosis of LUAD remains poor. Consequently, it is urgent to investigate the potential mechanisms of LUAD. Junctional adhesion molecule-like protein (JAML), is recognized as a tumorigenesis molecule in gastric cancer. However, the role of JAML in LUAD is still unclear. Here we aimed to evaluate the role of JAML in LUAD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Survival analysis revealed that high expression of JAML predicted poor survival in patients with CRC. These results were also supported by previous studies on gastric cancer and lung adenocarcinoma tissues 14,15 . However, our study also showed that the expression of JAML was not correlated with T stage in patients with CRC, which may have been due to the bias that almost all patients in our study had T3 or T4 disease.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Survival analysis revealed that high expression of JAML predicted poor survival in patients with CRC. These results were also supported by previous studies on gastric cancer and lung adenocarcinoma tissues 14,15 . However, our study also showed that the expression of JAML was not correlated with T stage in patients with CRC, which may have been due to the bias that almost all patients in our study had T3 or T4 disease.…”
Section: Discussionsupporting
confidence: 89%
“…Our research group was the rst to nd that JAML was highly expressed in gastric cancer tissues and was also associated with poor prognosis 14 . Subsequently, Wu reported high expression of JAML in patients with lung adenocarcinoma 15 . However, the expression and the biological function of JAML in CRC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To further verify the biological function of RPS24, we found that inhibiting the expression of RPS24 in HCC cells could inhibit the growth of subcutaneous tumor tissue in vivo. In addition, we discovered that highly expressed RPS24 could significantly enrich multiple cancer-promoting signaling pathways, such as the E2F targets, Wnt/β-catenin signaling, G2M checkpoint, and MYC targets, which accelerated tumor cell mitosis [23][24][25]. Furthermore, we found that the RPS24 hypermethylation or hypomethylation status affected the cancer cells' malignant characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…β-Catenin protein expression is also upregulated by FOXH1 [ 123 ], LRP8 [ 124 ], CBX4 [ 125 ], SMEK1 [ 126 ], JAML [ 127 ], ERCC6L [ 128 ], NOVA1 [ 129 ], SETDB1 [ 130 ], HMGB1 [ 131 ] and DEPDC1B [ 132 ] (Table 2 ), though the underlying molecular mechanism remains elusive. Additional regulators specifically mediate the level of active (i.e., unphosphorylated at Ser33/Ser37/Thr41) β‐catenin.…”
Section: The Positive Regulators Of Wnt/β-catenin Signalingmentioning
confidence: 99%